149k views
3 votes
Solve -37 + n equals -56 for n​

2 Answers

4 votes

Answer:

N=-19

Explanation:

Just add 37 to bot sides

User Ava Barbilla
by
5.5k points
2 votes

Simplifying

-37 + n = -56

Solving

-37 + n = -56

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '37' to each side of the equation.

-37 + 37 + n = -56 + 37

Combine like terms: -37 + 37 = 0

0 + n = -56 + 37

n = -56 + 37

Combine like terms: -56 + 37 = -19

n = -19

Simplifying

n = -19

User Casbby
by
5.0k points